2009
DOI: 10.1177/1933719109341998
|View full text |Cite
|
Sign up to set email alerts
|

Elafin (SKALP/Trappin-2/proteinase inhibitor-3) Is Produced by the Cervix in Pregnancy and Cervicovaginal Levels Are Diminished in Bacterial Vaginosis

Abstract: Elafin is a component of cervicovaginal secretions in pregnancy, and levels are diminished in bacterial vaginosis. It may be an important component of innate immunity in the lower genital tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 46 publications
2
38
1
2
Order By: Relevance
“…Kenyan pregnant women in our study showed lower levels of elafin. Elafin has been shown to be expressed in the genital tract of pregnant women (20), and its anti-HIV activity was previously described (21,22), making it a probable correlate of immunity against HIV infection. In another relatively small study of predominantly white U.S. women (23), the levels of IL-1␣ and IL-1RA were relatively higher in the CVL samples of pregnant women with a mean gestational age of 23.5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Kenyan pregnant women in our study showed lower levels of elafin. Elafin has been shown to be expressed in the genital tract of pregnant women (20), and its anti-HIV activity was previously described (21,22), making it a probable correlate of immunity against HIV infection. In another relatively small study of predominantly white U.S. women (23), the levels of IL-1␣ and IL-1RA were relatively higher in the CVL samples of pregnant women with a mean gestational age of 23.5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of a classic inflammatory response in BV (3), possibly abrogated by antibody-and cytokine-cleaving proteases of BV organisms (13), BV is strongly associated with increased levels of proinflammatory cytokines such as interleukin-1␤ (IL-1␤), IL-6, and IL-8 (40) and decreased mucosal defense factors such as elafin (52). In contrast, vaginal lacto-bacilli metabolize epithelial glycogen and produce lactic acid and reactive oxygen species such as hydrogen peroxide (H 2 O 2 ), widely believed to protect the reproductive tract from exogenous pathogens (7,9,28).…”
mentioning
confidence: 99%
“…Moreover, there is emerging evidence that suggests that the reproductive tract production of elafin is altered in bacterial vaginosis (BV) 7 , chorioamnionitis 9 and in women at high risk of preterm labour 8 .…”
Section: Introductionmentioning
confidence: 99%
“…There is growing literature demonstrating the expression of host defence peptides (HDPs) in the human female reproductive tract, including the cervical mucus plug, [6][7][8] . Moreover, there is emerging evidence that suggests that the reproductive tract production of elafin is altered in bacterial vaginosis (BV) 7 , chorioamnionitis 9 and in women at high risk of preterm labour 8 .…”
Section: Introductionmentioning
confidence: 99%